Junior coaches' perceptions of core tennis parenting principles - Lauer, L.; Gould, D.; Rolo, C.; Jannes, C.; Pennisi, N. (Medicine and Science in Tennis, 2006)
This study's aim was to better understand the role of parents in junior tennis player development and ways in which coaches work effectively with them. Specifically, core principles of tennis parenting were identified across six focus group interviews conducted with 24 experienced American junior coaches. Transcriptions of the interviews were content analysed and are presented in three general categories of core principles, parents and their involvement in tennis, factors influencing parent problems, and parent-coach-player interactions. Coaches indicated that parents are important to junior tennis and provided principles for optimal tennis parenting. They also discussed how the coach influences and can improve relations with parents.